2017
DOI: 10.1073/pnas.1701517114
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of Alzheimer’s disease using spectrochemical analysis of blood

Abstract: The progressive aging of the world's population makes a higher prevalence of neurodegenerative diseases inevitable. The necessity for an accurate, but at the same time, inexpensive and minimally invasive, diagnostic test is urgently required, not only to confirm the presence of the disease but also to discriminate between different types of dementia to provide the appropriate management and treatment. In this study, attenuated total reflection FTIR (ATR-FTIR) spectroscopy combined with chemometric techniques w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 59 publications
4
111
0
Order By: Relevance
“…Moreover, previous spectroscopic studies have successfully investigated ovarian tissue post-surgery and showed significant differences between normal and malignant cases [20][21][22]. However, the use of biological fluids, such as blood samples, are numerous: minimally-invasive collection, easier sample preparation and collection of serial samples from the same participants, just to name a few [23,24]. Raman spectroscopy investigates the phenomenon of inelastic light scattering that is caused after the interaction of light with matter.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous spectroscopic studies have successfully investigated ovarian tissue post-surgery and showed significant differences between normal and malignant cases [20][21][22]. However, the use of biological fluids, such as blood samples, are numerous: minimally-invasive collection, easier sample preparation and collection of serial samples from the same participants, just to name a few [23,24]. Raman spectroscopy investigates the phenomenon of inelastic light scattering that is caused after the interaction of light with matter.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the liver, spleen, lung and kidney further, IR was employed to interrogate these four tissues; significant post‐exposure alterations were again observed. IR spectra allowed an estimation of lipid/protein ratio (1740/1400 cm −1 ), C=O stretching/CH 2 methylene ratio (lipid oxidation level) (1745/1468 cm −1 ), amide I/amide II ratio (1655/1545 cm −1 ), α‐helix/β‐sheet ratio (1658/1635 cm −1 ) and CH 3 methyl/CH 2 methylene ratio (acetylation level) [(2960 + 2937 + 2874 cm −1 )/(2924 + 2853 cm −1 )] in tissue (Gautam et al, ; Mecozzi et al, ; Paraskevaidi et al, ; Zhang, Huang, Yan, Zhang, & Li, ).…”
Section: Resultsmentioning
confidence: 99%
“…Among a broad range of neurodegenerative diseases, AD constitutes 60-70% of all types of dementia [15]. Of the world population, 26.6 million were affected by AD in 2006, but currently it is expected that the AD prevalence may quadruple by 2050; thus, 1 in 85 persons will suffer from AD [16].…”
Section: Alzheimer's Diseasementioning
confidence: 99%